Implementasi Pijat Refleksi Kaki Untuk Menurunkan Tekanan Darah Pada Pasien Hipertensi Di Rumah Sakit Tk II Putri Hijau Medan - Munawir Rifqi; Nina Fentiana; Ika Ariyanti (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Hypertension is one of the most common diseases experienced by the community and poses a high risk of causing serious complications. Persistently elevated blood pressure can damage vital organs and increase the risk of cardiovascular diseases such as heart attacks, strokes and kidney failure. The purpose of this study is to determine the implementation of foot reflexology massage to reduce blood pressure in patients with hypertension. This research employed a case study approach involving two hypertensive patients at TK II Putri Hijau Hospital Medan. The Nursing care process included assessment, nursing diagnosis, planning, implementation, and evaluation. The results showed a decrease in both systolic and diatolic blod pressure after the foot reflexology intervention. The first patient experienced a reduction in blood pressure from 145/90 mmHg to 130/82 mmHg, while the second patient’s blood pressure from 144/89 mmHg to 128/82 mmHg. The study cocludes that the implementation of foot reflexology massage is proven to be efeective in lowering blood pressure in hypertensive patients. This therapy is recommended as a complementary intervention in nursing practice to assist in controlling hypertension.